Mapping A Knowledge Map For Researching The Legal Framework Related To Maritime Transportation Supply Chain E-Contract - Tripiawan, Wawan; Rachmawati, Irma (Magister Kenotariatan Universitas Pasundan, 2025)
This study analyzed a reflection on a bibliometric approach to evaluate the importance and impact of the manuscripts that have been published with the title “Law of Maritime Transportation” during the period 1998-2024. It also reveals that the area of Law of maritime documents has received increased attention and interest from academicians, researchers, and research funding institutions. The paper aims to provide a wide range of maritime fields and to offer a representation of various areas and interdisciplinarity research. Furthermore, to find out how they are connected. Bibliometric analyses were used in this study to examine dominant subfields of maritime Law, mapping and clustering the keyword. The tool provided the authors' data, year of publication, country of origin, Journal of publication, and affiliated institutions. The findings show that the manuscripts regarding the legal framework of maritime transportation documents are divided into 6 clusters. The most prominent focus is the Law of the Sea, International Law, and Law of Legislation. The legal framework was an umbrella that covered shipping, maritime transportation, documentary framework, maritime policy, and sustainable development.